Clinical and neurobehavioural study of the acute and chronic neurotoxicity of styrene. Issue 11 (November 1989) - Triebig, G; Lehrl, S; Weltle, D; Schaller, K H; Valentin, H
Abstract : A cross sectional field study of workers exposed to styrene was performed to evaluate possible acute and chronic neurotoxic effects. A total of 36 workers of four companies handling polyester resin materials for one to 16 years (median: 7 years) and two control groups were each examined on a Monday. The control group 1 (formed to compare acute effects) consisted of 20 men from two companies with no exposure to neurotoxic chemicals. To compare chronic effects, a second control group was formed by "one to one matching" with respect to age, socioeconomic status, and pre-exposure intelligence level. Ambient air monitoring using active sampling (short time) and passive samplers (long time) showed styrene in air concentrations as follows: range 3-251 ppm (median: 18 ppm) and concentrations 140-600 ppm during lamination of the inside of boats. For biological monitoring the results were as follows (postshift samples: range/median): styrene in blood: 5-482 micrograms/dl (39 micrograms/dl), mandelic acid urine: 0.01-3.64 g/l (0.21 g/l), and phenylglyoxylic acid urine: 0.01-0.87 g/l (0.19 g/l). The clinical examination found no signs or symptoms of peripheral neuropathy or encephalopathy. The principal work related health complaints were acute, reversible irritation of the eyes that occurred after exposure to styrene concentrations of 200 ppm or more. The neurobehavioural tests showed no significant differences in acute effects (p greater than 0.05) between the two groups or between preshift and postshift testing. Nor were there any significant differences in the relevant neurobehavioural variables between the styrene workers and the controls. It is concluded that occupational exposure to styrene concentrations in air up to 100 ppm causes no adverse acute or chronic effects on the central nervous system.